Benefits of Applied Behavior Analysis for Early Intervention in Autism Spectrum Disorder (ASD) (Research, Society and Development, 2023)
The present study seeks to reflect on the theme of the importance and benefits of Applied Behavior Analysis (ABA) in the early intervention of children diagnosed with Autism Spectrum Disorder. Early intervention based on ABA principles can improve functioning in children with ASD by addressing behavioral deficits and excesses. In this way, the objective of this work seeks to understand the performance of the ABA method in the aid and development of children living on the spectrum. This is an integrative literature review as a research method on the subject, since this research model seeks to organize and examine the speeches and contributions made by other authors. The collected data were obtained from the databases: Scientific Electronic Library Online, Latin American Literature in Health Sciences via BVS and Medical Literature and Retrivial System on-Line via PubMed, period from 2017 to 2022. sample of eight studies, the results showed positive deductions regarding the relevance of Applied Behavior Analysis and the possibility of developing more cognitive, behavioral and social skills, based on early diagnosis and intervention.